Efektifitas Pemberian Tablet Besi (Fe) Terhadap Peningkatan Kadar Hemoglobin pada Siswi yang Menderita Anemia di SMAN 3 Kabupaten Sampang - Setiyowati, Eppy; Nadatien, Ima; Rusdianingsih, Rusdianingsih; Amilia, Yunita (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2019)
Young women every month experiencing menstruation will be at risk for anemia, coupled with poor dietary habits. The aim of the study was to analyze the effectiveness of giving Fe tablets to hemoglobin levels of female students who suffer from anemia in SMAN 3 in Sampang Regency. Descriptions of quasi-experimental studies using the one sample pre-post design cohort approach, the population is the third-grade students of Sampang State High School who suffer from anemia as many as 115 students. The sample size is determined by the formula as many as 89 respondents. Provision of Fe tablets for 1 week with a dose of 1 day 1 time, when students experience menstruation. Data retrieval was done by measuring Hb levels before and after administration of Fe tablets. Furthermore, the data was analyzed by a paired test t-test. The results of the study showed that the administration of iron tablets was significant for changes in Hb levels that the results of the test analysis showed a p-count of 0.00. This is due to the fact that the administration of Fe tablets for 1 week can change Hb levels in Sampang 3 High School students. The conclusions of the study showed that the administration of Fe tablets was able to change Hb levels so that students who were anemic at the time of menstruation should be given a Fe tablet so that there was no decrease in hemoglobin levels.Â Keyword: Anemia, tablet Fe, Kadar Hb